Physicochemical and Biological Insights Into the Molecular Interactions Between Extracellular DNA and Exopolysaccharides in Myxococcus xanthus Biofilms - Wang, Yan; Li, Tingyi; Xue, Weiwei; Zheng, Yue; Wang, Yipeng; Zhang, Ning; Zhao, Yue; Wang, Jing; Li, Yuezhong; Wang, Chuandong; Hu, Wei (Frontiers in Microbiology, 2022)
Extracellular DNA (eDNA) is a critical component in the extracellular matrix (ECM) of bacterial biofilms, while little is known about the mechanisms underlying how eDNA integrates into the ECM through potential macromolecular interactions. Myxococcus xanthus biofilm was employed as a suitable model for the investigation due to the co-distribution of eDNA and exopolysaccharides (EPS) owing to their direct interactions in the ECM. DNA is able to combine with M. xanthus EPS to form a macromolecular conjugate, which is dominated by the electrostatic forces participating in the polymer-polymer interactions. Without intercalation binding, DNA-EPS interactions exhibit a certain degree of reversibility. Acting as a strong extracellular framework during biofilm formation process, the eDNA-EPS complex not only facilitates the initial cell adhesion and subsequent establishment of ECM architecture, but also renders cells within biofilms stress resistances that are relevant to the survival of M. xanthus in some hostile environments. Furthermore, the EPS protects the conjugated DNA from the degradation by nucleic acid hydrolases, which leads to the continuous and stable existence of eDNA in the native ECM of M. xanthus biofilms. These results will shed light on developing prevention and treatment strategies against biofilm-related risks.